Investigasi Aspek-aspek Promosi Penjualan - Simamora, Bilson (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2023)
In today's highly developed e-commerce era, sales promotions have become a reliable marketing communication technique for many companies. There is also much research in this field. However, many researchers need to define and operationalize sales promotions as a research variable correctly. With critical review techniques, this study found that aspects of sales promotions that can be used as observation variables are perceived value, credibility, fairness, time frame, uncertainty, congruence, requirements, and consequences. Every sales promotion technique requires different aspects. The researchers should match the sales promotions technique properly with their relevant aspects.